Flood mapping using geographic information system (GIS) - Md. Zahri, Azura (2015)
Naturally Malaysia facing with flood problem all over the country. This problem will make worst loses to property and life. Sarawak is one of the state in Malaysia which facing with this problem. In 1963,2004 and 2009, Sarawak experience the worst flood event all over the year. Hence the flood mitigation rush to built in order to control the flood. However before the flood mitigation plan is built, there are several information need to be develop in order to predict the flood area. Several research had been done in order to develop the flood hazard mapping. Certain use InfoWorks RS and other use Autocad 3D associate with Google Earth. In this study, the main aim is to provide flood hazard mapping and identify the rivers that contribute to flood. The flood map was evaluated based on areas and perimeter of the floodplain. The data was collected from Urban Section of DID Sarawak. The digitizing process was used in order to complete the flood mapping process. GIS application also used to achieve other objectives. The analysis show the flood prone area in Sarawak include the river that contribute to floodpain. It was 5163.6 km2 and 9442.8 km of floodplain in Sarawak. Usually there were 550km2 and 600km was cover with flood. For the conclusion Samarahan and Mukah was the division that always experience with the flood problem due to the number of river that contribute to flood and percentage of area that covered by flood. This research can help people to understand and get informed the frequent flood area and being prepared for the flood occurrences.